Earnings inequality and the equity premium - Karl Walentin (Sveriges Riksbank, 2007)
We present data from the Survey of Consumer Finances showing that the increased earnings (labor income) inequality, in combination with increased stockmarket participation, has roughly doubled stockholders' share of aggregate labor income in the last four decades. We explore the impact of the increase in this share on returns to equity and returns to a risk-free bond in a model with limited stockmarket participation, labor income and borrowing constraints. The main result is that the increase in stockholders' share of aggregate labor income has lead to 130 basis points (45 percent) decrease in the ex ante equity premium (i.e. the discount rate applied to equity). The reason for this change is that the increase in stockholders' share of aggregate labor income leads to a change in income composition for stockholders - an increase in the fraction of their income that consists of labor income and a decrease in the fraction that consists of dividend income. This reduces the covariance between stockholder income growth and dividend growth. The size of the decrease in the equity premium implied by our model roughly coincides with the historical change in the post-1951 equity premium implied by the simple dividend growth model in Fama and French (2002).
Keywords: D31; E24; E44; G12; 330; labor income; earnings inequality; asset pricing; equity premium; limited participation; borrowing constraints; Lohn; Einkommensverteilung; Aktionäre; Risikoprämie; CAPM; USA